أثر القيادة التحويلية في استراتيجيات الأزمات في المركز الوطني للأمن وإدارة الأزمات - المحاسنة، محمد عبدالرحيم عبدالرحمن; المومني، عبدالسلام إبراهيم عبدالله (الجامعة المستنصرية - مركز المستنصرية للدراسات العربية والدولية, 2024)
هدفت الدراسة إلى بيان أثر القيادة التحويلية في استراتيجيات إدارة الأزمات في المركز الوطني للأمن وإدارة الأزمات وتم اعتماد المنهج الوصفي التحليلي، وتكون مجتمع الدراسة من القيادات في المركز الوطني للأمن وإدارة الأزمات والموظفين الذين هم على تماس مباشر بإدارة الأزمات وتم توزيع (147) استبانة على مجتمع الدراسة والبالغ (167) عنصرا استرجع ما نسبته (91.83%) من الاستبانات الصالحة للتحليل الإحصائي. وأظهرت الدراسة أن تصورات المبحوثين لمستوى الأبعاد التي تقيس القيادة التحويلية قد جاء بدرجة مرتفعة وأن تصورات المبحوثين لمستوى الأبعاد التي تقيس متغير استراتيجيات إدارة الأزمات قد جاء بدرجة مرتفعة ووجود أثر ذي دلالة إحصائية للقيادة التحويلية بأبعادها مجتمعة في تطوير استراتيجيات إدارة الأزمات بأبعادها مجتمعة. أوصت الدراسة بضرورة استمرار المركز الوطني للأمن وإدارة الأزمات بالمحافظة على ممارسة نمط القيادة التحويلية وتطبيق استراتيجيات إدارة الأزمات، والتركيز على ضرورة إشراك الموظفين في عملية اتخاذ القرارات وتطوير آلية توليد الأفكار لديهم، بهدف تطويرهم وتحويلهم إلى قادة في مواقعهم. The study aimed to demonstrate the impact of transformational leadership on crisis management strategies at the National Center for Security and Crisis Management. The descriptive analytical approach was adopted. The study population consisted of leaders at the National Center for Security and Crisis Management and employees who are in direct contact with crisis management. (147) questionnaires were distributed to the community. The study, which included (167) subjects, retrieved a percentage of (91.83%) of the questionnaires suitable for statistical analysis. The study showed that the respondents’ perceptions of the level of the dimensions that measure transformational leadership reached a high degree, and that the respondents’ perceptions of the level of the dimensions that measure the variable of crisis management strategies reached a high degree, and that there was a statistically significant effect of transformational leadership in its combined dimensions in developing crisis management strategies in its combined dimensions. The study recommended the need for the National Center for Security and Crisis Management to continue to practice the transformational leadership style, apply crisis management strategies, and focus on the need to involve employees in the decision-making process and develop their idea generation mechanism, with the aim of developing them and transforming them into leaders in their positions.
Keywords: إدارة الأزمات -- الاستراتيجيات الإدارية -- الاستثارة الفكرية